CAUSES OF THE OCCURRENCE OF CARDIOVASCULAR DISEASES (Academicia Globe: Inderscience Research, 2023)
The main causes of cardiovascular diseases are changes in the external environment, lack of activity - hypodynamia, physical and mental stress, consumption of products with a lot of animal fat in the diet, smoking and alcohol addiction. There are many diseases such as heart disease and brain stroke caused by it, heart defects. When eating, it is necessary to pay attention to the diversity of the diet, to have enough proteins, to replace meat with fish, legumes, and poultry, to increase the number of vegetables and fruits, and to limit the consumption of soup.